Recreating the commons? : NGOs in Bangladesh - Khan, Farida; Ahmad, Ahrar; Quddus, Munir; Bangladesh Development Initiative (Dhaka : Bangladesh Development Initiative ; University Press, 2009)
Contributed articles.
section 1. History and background -- section 2. Religion, gender, and civil society -- section 3. Contributions of NGOs.
Includes bibliographical references and index.
GenEd
Keywords: Non-governmental organizations -- Bangladesh; Islam and social problems -- Bangladesh; Social conflict -- Bangladesh; Human rights -- Bangladesh